Collision of vortex-rings with fluid interfaces - Koh, Jing Yu (2019)
The collision of vortex-rings with various surfaces has always been an intriguing topic, despite the simple flow configuration and initial conditions. Generally, it only requires generating a coherent vortex-ring to collide with a surface under the selected translational velocity. This simple flow configuration produces an astonishingly complex flow behaviour leading to the formation of multiple vortex structures. Although many studies were done on vortex-rings colliding with “non-slip” solid boundaries, collision with other “slip” boundary interfaces such as free surface and fluid with different density are much less studied. Therefore, this project provides more information on the interactions of vortex-rings with fluids of different densities using laser-induced fluorescence and time-resolved particle-image velocimetry to look into the transition to incoherence and turbulence. Circular vortex-rings were subjected to collision normal to a water-oil interface. Using a cylindrical piston driven by motorized linear actuator [1], the behaviours of vortex-rings before, during and after the collision are examined. The behaviours are investigated by deriving the velocity and vorticity fields of the vortex-rings as they collide with the interface and are later compared with the flow visualizations acquired during and after the collision. Stream-wise and cross-stream directions of the same flow will be analysed simultaneously to give a different point of view and different discovery. Different Reynolds’ numbers of vortex-rings yield very different flow characteristics. For low Reynolds’ number of 1000, the water-oil interface behaved almost identical to a solid flat boundary. For Reynolds’ number of 2000, a bump was observed from the collision, causing the water-oil interface to waver slightly. For high Reynolds’ number of 4000 and 5000, the primary vortex-ring penetrated the oil layer, which caused the water-oil interface to waver and give a completely different flow characteristics compared to Reynolds’ number 1000 and 2000. The cross-stream observations were completely different as the interaction between the primary and secondary vortex-ring introduces the three-dimensional instability and the formation of counter-rotating vortex-pairs. This leads to a hastened interaction and dissipation of the secondary vortex-ring before transitioning to turbulence. Understanding the transitions from this study will help gather more information on the differences between collisions with solid and free surfaces.